(untitled) (Journal of Geography and Environmental Management, 2025)
The article analyzes the evolution of scientific publications on the topic of hydrological drought. The analysis of the chronological dynamics and structure of publications revealed a growing scientific interest in this field and a significant expansion of research directions at the international level. As the methodological basis for preparing the article, various scientific publications on hydrological drought were used, and the Web of Science scientometric database was selected for bibliometric analysis. Over the past two decades, the main research directions have focused on improving drought indices, assessing the impacts of climate change, developing modeling and forecasting methods, applying satellite technologies, and analyzing anthropogenic influences. In the context of Kazakhstan, the issue of hydrological drought is of particular relevance, as it directly affects the availability and sustainable use of water resources. The increase in publication activity in global science and the integration of new methods (remote sensing, climate modeling, artificial intelligence) provide opportunities to improve water resource monitoring and forecasting systems at the national level. Integrating Kazakhstani research into the international scientific space not only enhances the country’s scientific development but also forms a foundation for adaptation strategies under changing climate conditions and increasing natural risks.